Promoting open and inclusive connectivity: The case for digital development cooperation - Maaike Okano-Heijmans; Wilhelm M. Vosse (Research in Globalization, 2021)
A focus on digital development cooperation as a cornerstone in Europe's digital connectivity agenda offers opportunities to act on long-term challenges and addresses several key priorities identified by the European Commission in third countries. This article develops an argument for strengthening Europe's agenda on digital development cooperation, specifically in the Indo-Pacific region. After first conceptualizing digital development cooperation, we argue that the key reasons for the EU to step up its digital development efforts in the Indo-Pacific region are the societal impact of disruptive technologies; the power shift towards the Indo-Pacific; the expanding clout of the Chinese Digital Silk Road; and the implications of the US-China tech conflict. The EU's 2030 Digital Compass provides an ideal framework to envision the digital development cooperation initiatives of European and Asian players. The EU can benefit from cooperation and coordination with like-minded partners in the Indo-Pacific.
Keywords: 330; Digital development cooperation; European Union; Indo-Pacific; Connectivity